The effect of cesarean delivery on sexual function in maternity mothers at Al Fatah General Hospital Ambon - Kokmesa, Siska Della; Dinopawe, Asriaty; Thalib, Abdul; Difinubun, Kurniah Hasbi Abdullah (Innovative Approaches in Health Science Journal, 2024)
Background: Caesarean section is a filling surgery with a cut in the abdominal chamber and a cut of the uterine base to retrieve the embryo in the womb. Cesarean section is performed if vaginal birth does not strengthen and delaying birth can endanger the mother and child. Sexual function is the level or degree of the overall normal sexual response cycle. Sexual function is relevant to aspects of sexual response in humans. Abnormal sexual response is a disorder of sexual function. Sexual function can be used to examine human sexuality in clinical contests. Method: The purpose of  this study was to analyze the effect of cesarean delivery on sexual function in maternity mothers at Al-Fatah General Hospital Ambon. The research method used is an analytical survey design with a cross sectional design. The population is all maternity mothers at Al-Fatah General Hospital Ambon which amounts to 100 people. Sampling using purposive sampling. The sample in this study amounted to 32 people. Results: The results of the study obtained mothers who had good sexual function amounted to  28 people (93.3%) and mothers who had poor sexual function amounted to 2 people (6.7%). Evidenced by the results of the independent t test, the sig value is obtained. (2-tailed) : 0.000 (α < 0.05) which means that there is an effect of cesarean delivery on sexual function in maternity mothers at Al-Fatah General Hospital Ambon. Conclusion: The conclusion of the results of the study was obtained that there was a significant influence between cesarean delivery on sexual function in maternity mothers at Al-Fatah General Hospital Ambon with sig values. (2-tailed) : 0.000